2020
DOI: 10.21037/apm-20-1714
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture of the Beishu acupoint participates in regulatory effects of ginsenoside Rg1 on T cell subsets of rats with chronic fatigue syndrome

Abstract: Background: There are close relationships between the spleen and limb muscles and thoughts. The study aims to test the effects of ginsenoside Rg1 in combination with acupuncture of the Beishu acupoint on T cell subsets of rats with chronic fatigue syndrome (CFS). Methods:The model was set up by combining forced cold-water swimming with chronic restraint. The rats were randomly divided into blank control, model, ginsenoside, acupuncture, and ginsenoside plus acupuncture groups (n=10). For the acupuncture group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…ere is a concern that macromolecules that include 114 might stimulate the proliferation of CD8 + T cells in autoimmune diseases, similar to how ginsenoside Rg1 included in ginseng (a component of 114) has been reported to increase the ratio of CD8 + T cells in vivo [23]. In contrast, the results of this study showed that 114 did not affect the increase in the ratio of CD8 + T cells when used in combination with PSL, suggesting that 300 μg/mL 114 is a safe dosage that does not elevate the ratio of CD8 + T cells when used in combination with PSL in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…ere is a concern that macromolecules that include 114 might stimulate the proliferation of CD8 + T cells in autoimmune diseases, similar to how ginsenoside Rg1 included in ginseng (a component of 114) has been reported to increase the ratio of CD8 + T cells in vivo [23]. In contrast, the results of this study showed that 114 did not affect the increase in the ratio of CD8 + T cells when used in combination with PSL, suggesting that 300 μg/mL 114 is a safe dosage that does not elevate the ratio of CD8 + T cells when used in combination with PSL in vitro.…”
Section: Discussionmentioning
confidence: 95%
“…Ginseng, a component of NYT, is widely used for treating fatigue because it has been reported to improve energy, physical and emotional health, and well-being [ 44 ]. Ginsenoside Rg1, the main active ingredient in Ginseng, has been reported to have anti-fatigue effects by regulating the number of T cell subsets and enhancing immunity in rats with chronic fatigue syndrome [ 45 ]. Furthermore, one of the constituents of NYT, Schisandra Fruit, has been reported to improve endurance and energy metabolism in exercised rats and has the potential to upregulate peroxisome proliferator-activated receptor-gamma coactivator-1 α in skeletal muscle, which is a key regulator of energy metabolism [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…NYT has been suggested to improve the appetite via dopamine and NPY pathway [ 51 53 ] and to inhibit corticosterone by inhibiting NO synthesis [ 30 ]. In addition, schisandra fruit and citrus unshiu peel have been reported to have anti-anxiety effects [ 28 , 54 , 55 ] and ginseng has been reported to have anti-anxiety and anti-fatigue effects [ 56 , 57 ]. All of these are ingredients of NYT.…”
Section: Discussionmentioning
confidence: 99%